2018
DOI: 10.1038/s41598-018-25609-z
|View full text |Cite
|
Sign up to set email alerts
|

A targeted boost-and-sort immunization strategy using Escherichia coli BamA identifies rare growth inhibitory antibodies

Abstract: Outer membrane proteins (OMPs) in Gram-negative bacteria are essential for a number of cellular functions including nutrient transport and drug efflux. Escherichia coli BamA is an essential component of the OMP β-barrel assembly machinery and a potential novel antibacterial target that has been proposed to undergo large (~15 Å) conformational changes. Here, we explored methods to isolate anti-BamA monoclonal antibodies (mAbs) that might alter the function of this OMP and ultimately lead to bacterial growth inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…OMPs include a functional role in bacterial pathogenesis, OM permeability barrier, efflux pumps, diffusions of nutrients, membrane integrity and in active transport. For chimeric vaccine construction, bacterial OMPs has selected because of their antigenic and immunogenic behavior 34 . OMPs that plays an essential and virulent factor role may be useful in therapeutics design.…”
Section: Methodsmentioning
confidence: 99%
“…OMPs include a functional role in bacterial pathogenesis, OM permeability barrier, efflux pumps, diffusions of nutrients, membrane integrity and in active transport. For chimeric vaccine construction, bacterial OMPs has selected because of their antigenic and immunogenic behavior 34 . OMPs that plays an essential and virulent factor role may be useful in therapeutics design.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is well recognized that the BAM complex itself as well as chaperones in delivering proteins to the outer membrane are critical for membrane integrity as well as antibiotic resistance and could therefore be targets for drug development (Tamae et al, 2008; Weirich et al, 2017; Storek et al, 2018; Vij et al, 2018). Nevertheless, previous studies revealed species-specific differences in the importance of individual components in OMP biogenesis such as Skp and SurA (Sklar et al, 2007; Volokhina et al, 2011; Weirich et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies aimed to identify the useful substance in these structural components for immunization against bacterial infection; however, almost all studies did not achieve the establishment of an effective strategy in the immunization. In fact, the immunization strategies using bacterial components have several side effects and lack a long-term immunization effect [18,19]. Furthermore, the exact immune response by the immunization is difficult to characterize in individuals [20,21].…”
Section: Discussionmentioning
confidence: 99%